Electrochemical recovery of phosphorus from wastewater using tubular stainless-steel cathode for a scalable long-term operation. (1st July 2021) - Lei, Yang; Zhan, Zhengshuo; Saakes, Michel; van der Weijden, Renata D; Buisman, Cees J. N.
Highlights: Electrochemically deposited solids adhere well to vertically placed electrodes. The deposition layer delays the diffusion of hydroxide ions. The prototype achieves high stability and efficiency over 173 days of operation. Calcium phosphate is the dominant phase in the recovered solids. Recovered solids have high p content (> 9wt%) and negligible heavy metals. Abstract: Phosphorus (P) is an irreplaceable element, playing a vital role in living organisms, yet has limited earth reserves. The possibility of P recovery from wastewaters by e lectrochemically-induced ca lcium p hosphate p recipitation (ECaPP) was demonstrated previously. The current study presents a novel scalable prototype consisting of a column-shaped electrochemical reactor, a tubular stainless-steel cathode, and a Pt coated Ti anode. The adhesion of solids to the cathode, important for product recovery, was shown not to be negatively impacted by electrodes' vertical placement. The influence of current (density), hydraulic retention time (HRT), and initial phosphate concentration in this prototype were examined under continuous flow operation. The system accomplished the highest P removal rate (1267 mg/day) at 1.5 d HRT and 800 mA in treating undiluted cheese wastewater with 48.5 kWh/kg P. Moreover, the prototype showed high stability and efficiency (> 50%) over 173 days of continuous operation without performing maintenance. After turning off the current (0 mA), the system realized a surprising P removal jump up to 97.3%, revealing the delayed diffusion of hydroxide ions by the deposition layer. The calculation of CAPEX and OPEX of ECaPP in treating 100 m 3 cheese wastewater per week indicates that the ECaPP plant can realize net-positive from the 12 th year. The recovered solids have relatively high P content (> 9wt%) and insignificant contamination of heavy metals. Overall, the proven suitability of the scalable prototype can pave the way towards the actual adoption of the ECaPP process. Graphical abstract: Image, graphical abstract